THE RAISING CONCERN OF FOOD WASTE AND FOOD LOSS IN INDONESIA TO ACHIEVE A SUSTAINABLE CONSUMPTION - Agung Ayu Putri Kinanti; Tahnia C Heidra; Yunita Ismail Masjud (FIRM Journal of Management Studies, 2021)
The effect of food waste and food loss is more severe than other recent environmental issues such as plastic usage. Every year, Indonesia needs a 19 million kilos food supply, yet 1.3 billion tons per year being wasted and lost, which affects the value of food and production itself and hazardous to the environment. It is estimated yearly, food waste producing 3.3 billion tons of CO2 and wasted 1.4 billion hectares of ripe land for vain. Globally, many individuals, organizations, and governments in several countries campaign to raise awareness to face this problem, including Indonesia. With the government's help, many organizations encounter this environmental issue by online media approach, physical campaign, encouraging households to reduce food loss by giving knowledge, and many more. They are reflecting other countries also become one of the ideas that can be implemented by society.